2008
DOI: 10.1097/mao.0b013e318185fb0d
|View full text |Cite
|
Sign up to set email alerts
|

Bone Conduction Hearing Level in Patients With Eosinophilic Otitis Media Associated With Bronchial Asthma

Abstract: High-tone hearing loss and profound hearing loss were frequently associated with EOM, suggesting that inflammatory products of the middle ear invade the inner ear via the round window to cause inner ear damage. To prevent the deterioration of BCHL, the control of eosinophilic inflammation and bacterial infection is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
2
12
0
2
Order By: Relevance
“…In our study, high-tone loss was more frequently found and was more severe in EOM patients than in COM controls, and the infected ear with granulomatous otitis media was often accompanied by a signifi cant increase in bone conduction hearing level [13]. The cause of sensorineural hearing impairment is unclear.…”
Section: Change In Hearing Acuitymentioning
confidence: 94%
“…In our study, high-tone loss was more frequently found and was more severe in EOM patients than in COM controls, and the infected ear with granulomatous otitis media was often accompanied by a signifi cant increase in bone conduction hearing level [13]. The cause of sensorineural hearing impairment is unclear.…”
Section: Change In Hearing Acuitymentioning
confidence: 94%
“…High-tone hearing loss, in particular, is more frequent and more severe in EOM patients than in COM patients [7], with 47% of EOM patients showing deterioration in BCHL, and 6% developing bilateral profound hearing loss according to the clinical survey of EOM in Japan [4]. The cause of deterioration in BCHL in cases of EOM remains unclear, but significantly higher concentrations of eosinophil cationic protein (ECP) and IgE have been detected in the middle ear effusion of EOM patients than in that of control patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…To identify EOM in cases of NP could entail watching patients more closely. Indeed, an increased incidence of progressive and/or sudden sensorineural hearing loss had been described in cases of EOM [24], with bacterial infection and inflammatory mediators released in the middle ear contributing to inner ear damage [25]. This bone conduction hearing loss sometimes can lead to profound deafness.…”
Section: Otitis Media With Effusion In Nasal Polyposis: How To Manage?mentioning
confidence: 98%